Caracterização funcional da região promotora do gene Rasgef1b e avaliação de componentes da via de sinalização de receptores do tipo toll (TLRs) sobre sua regulação - Felipe Batista Leão (2016)
The guanine nucleotide exchange factor RasGEF1b is encoded by a gene whose expression is induced in innate immune cells in response to the activation of Toll-like receptors (TLRs). RasGEF1b mRNA levels are increased in human and murine macrophages upon stimulation with different TLRs agonists as well as in mice infected with protozoan parasites. However, the molecular mechanisms responsible for its transcriptional regulation are still unknown. Here we have characterized a regulatory region located upstream to the coding sequence of the murine Rasgef1b gene. Our in silico analysis indicates that the investigated region harbors putative binding sites for transcription factors that are critical in the immune response, such as AP-1, C/EBP, Sp1, STAT1 and NF-κB. To functionally investigate this region, we used genomic DNA obtained from a C57BL/6 mouse to amplify and clone, within luciferase reporter plasmid pGL3-basic, a DNA segment of 2.886 bp, generating the construction pGL3-2.8 kb. This segment comprises 119 nucleotides upstream and 2.747 nucleotides downstream Rasgef1b putative transcription start site (TSS) (-2.747 /+119). The pGL3-2.8 kb construction and the mutants generated by deletion were transfected into human HEK293 cells and murine RAW264.7 macrophages to evaluate, by gene reporter assays, their constitutive and induced activity upon the activation of TLRs pathways and NF-κB transcription factors. Our results indicate that the analyzed segments, except the one with the deletion of the region that harbors the putative TSS (pGL3-Δ492), present an increased activity compared to pGL3-basic vector. Furthermore, activation of TLR pathways resulted in a significant increase in their activity both in HEK293 cells and Raw264.7 macrophages. Moreover, in overexpression studies carried out in HEK293 cells, the NF-kB subunits p65 (RelA) or c-Rel were sufficient to induce a significant increase in the activity of the analyzed segments. Taken together, our results suggest that the analyzed region corresponds to the Rasgef1b promoter and that NF-kB family of transcription factors appear to play a role in the induced expression of this gene. Additionally, we provide experimental evidence confirming the presence of the putative TSS in the Rasgef1b gene by nested RT-PCR, and, by real time PCR, we demonstrated that mRNA levels of RasGEF1b in murine bone marrow derived macrophages (BMDMs) are dominant when compared to RasGEF1a and RasGEF1c.